The impact of smartphone addiction on mental health and its relationship with life satisfaction in the post-COVID-19 era - Zhu, Chunyue; Li, Shuo; Zhang, Lei (Frontiers in Psychiatry, 2025)
Following the COVID-19 outbreak, smartphone usage among quarantined Chinese college students surged significantly, leading to a growing dependency on their devices and adversely impacting their emotional well-being. Consequently, the negative emotions associated with smartphone addiction have emerged as critical factors influencing students’ life satisfaction. However, the psychological mechanisms linking these emotional effects to life satisfaction, as well as potential sustainable educational interventions, remain insufficiently explored. This study assessed a sample of 322 undergraduates (51.6% male) using the Mobile Phone Addiction Index (MPAI), the Depression, Anxiety, and Stress Scale (DASS-21), and the Satisfaction With Life Scale (SWLS) to construct a mediation model. The aim was to examine the relationships between smartphone addiction, negative emotions, and life satisfaction. Results revealed that smartphone addiction was significantly positively correlated with negative emotions (r = 0.332, p < 0.01), while negative emotions were significantly negatively correlated with life satisfaction (r = -0.391, p < 0.01). Among these negative emotions, depression emerged as a key factor, intensifying smartphone dependence and detrimentally affecting overall life satisfaction. The mediation analysis demonstrated that smartphone addiction contributes to the development of negative emotions, which in turn reduce life satisfaction. Students with higher levels of smartphone addiction reported heightened negative emotions, leading to more pessimistic coping strategies and, ultimately, a decline in mental health and life satisfaction. This study provides valuable insights into the impact of smartphone addiction on college students’ life satisfaction and offers actionable educational recommendations to mitigate its harmful effects, promoting healthier and more sustainable lifestyles for students.